Africa without borders: building blocks for regional growth - International Food Policy Research Institute (International Food Policy Research Institute, 2005)
Recent IFPRI research shows how coordinated investments in regional agricultural trade and productivity can leverage regional growth dynamics and improve Africa's competitiveness in an increasingly globalized world.. This brief looks at investing in trade by targeting Africa's own markets, improving economic integration, and reducing marketing costs; investing in research and development, strengthening regional institutions, and moving forward with an effective regional agenda.